Efficacy of nisin in combination with protective cultures against Listeria monocytogenes Scott A in tofu - Schillinger, U. (2001)
Nisin can be used as a biopreservative to control growth of Listeria monocytogenes in various minimally processed foods. Tofu is an example of a non-fermented soybean product, which may allow growth of Listeria at refrigeration temperatures and in which nisin may be applied to prevent multiplication of Listeria.The efficacy of nisin against Listeria may be compromised by the emergence of spontaneous nisin-resistant mutants. Exposure of L. monocytogenes Scott A to nisin in a culture medium or in a food product results in an initial reduction of Listeria population which is followed by regrowth of survivors to nisin during further incubation. In vitro studies using Standard I Nutrient broth showed that Enterococcus faecium BFE 900-6a and Lactobacillus sakei Lb 706-1a used as protective cultures in combination with nisin were able to suppress proliferation of Listeria cells not killed by nisin at 10 °C. Growth and bacteriocin production of these two strains and a third protective culture, Lactococcus lactis BFE 902 was also observed in soymilk and tofu at 10 °C.Inoculation studies with tofu prepared with nisin and protective cultures showed that lower amounts of nisin are required for an effective inhibition of L. monocytogenes Scott A when either E. faecium BFE 900-6a or Lc. lactis BFE 902 are used in addition. The combination of nisin with these bacteriocinogenic lactic acid bacteria (LAB) resulted in a complete suppression of listerial growth in homemade tofu stored at 10 °C for 1 week. Lb. sakei Lb 706-1a was less effective and did not prevent a slight increase of L. monocytogenes Scott A numbers during storage.